City tourism application functionality from the perspective of tourist experience and technology acceptance models - Pawlak, Katarzyna (Scientific Papers of Silesian University of Technology. Organization and Management Series, 2023)
Purpose: The purpose of the article is to identify the city tourism app functions affecting the process of users’ technology adoption. The article presents the issues related to tourism apps and the role thereof in building tourist experience, as well as selected models of technology acceptance. The paper goes on to discuss the results of a survey of selected Polish cities’ tourism applications. Design/methodology/approach: For the purpose of the study, a critical analysis of the literature on the subject was carried out, followed by analysis of selected applications and a qualitative study of application users’ comments. The study was conducted in accordance with the constructivist grounded theory. The process of user comment coding and analysis involved the use of the ATLAS.ti qualitative data analysis software. Findings: Based on the critical analysis of the literature and the survey of selected applications, a city tourism app functionality assessment model has been proposed. The need for urban app changes, to enhance the tourist experience, has been indicated as well. Research limitations/implications: The subject of the study comprised official city tourism applications. The survey encompassed applications which met the following criteria: the apps surveyed were official city apps, the potential thereof were tourists, the apps have been rated and commented. Practical implications: The results of the study can serve to increase the effectiveness of the promotional activities implemented by cities employing such applications to form relations with tourists. To a limited extent, they can also serve to facilitate the designing of apps intended for city residents. Social implications: The article draws attention to the issues of user involvement in the process of city tourism app development. The sphere of city applications can become a platform for tourist interaction, while the apps themselves can improve the quality of the tourists’ experience as well as their functioning in the city. Originality/value: The article fills the research gap in the studies on city tourism apps. It draws attention to the necessity of taking the following into account when designing such applications: the specifics of the tourist experience as a process, consideration of the app as an element of the tourist's technological experience, accentuation of those app functions, which are crucial from the perspective of the app acceptance process. Keywords: mobile apps, city tourism apps, tourist experience, technology acceptance process, technology adoption process. Paper category: Research paper.